The Siege of Zvornik in 1717 in a Poem in Turkish (Prilozi za orijentalnu filologiju, 2017)
This poem about the siege of Zvornik in 1717, composed in Turkish, belongs to the group of poems which deal with local problems and describe concrete people and events. The poem, written by certain Begzadić, who thus far has not been known as a poet in Turkish, describes the circumstances in the Austrian army and was waiting for the relief from Vezier Numan-pasha Ćeprilić (Köprülü-zade).